Preventing Money Laundering and Terrorist Financing : A Practical Guide for Bank Supervisors - Chatain, Pierre-Laurent (World Bank, 2012)
This book is specifically designed for bank supervisors, some of whom may be looking for ways to devise a program of anti-money laundering/combating the financing of terrorism (AML/CFT) supervision. Others may have encountered difficulties in elements of their systems of supervision and are looking for alternatives. Supervisors may also come to recognize even more efficient ways to carry out AML/CFT supervision. The objective of this book is therefore to provide a "how to" reference for practitioners of financial regulation and supervision. The authors have attempted to conceive a practical guide, with the purpose of resolving strategic and operational supervisory issues. They cover the entire spectrum of supervision, ranging from supervision objectives to the design and carrying out of onsite and offsite inspection programs, and from cooperation with other domestic and international AML/CFT authorities to sanctions and enforcement. The international community recognizes that under-regulated or unsupervised entities have the potential to undermine confidence in financial markets and hamper economic recovery. Better transparency, enhanced oversight, and stronger cross border cooperation among regulators and supervisors in all areas of risks, including money laundering and terrorist financing, are necessary to ensure that financial institutions always remain sound, sustainable, and vigilant. This task is even greater during difficult times.